2020
DOI: 10.1371/journal.pone.0237843
|View full text |Cite
|
Sign up to set email alerts
|

Poor glycaemic control contributes to a shift towards prothrombotic and antifibrinolytic state in pregnant women with type 1 diabetes mellitus

Abstract: Ojectives Thrombotic and antifibrinolytic influence of Diabetes mellitus type 1 (T1DM) on haemostasis have been well demonstrated. There has been no research assessing the influence of poor glycemic control on thrombus formation under flow conditions in vitro or in pregnant type 1 diabetic women to date. Patients/Methods This study compared singleton pregnant T1DM women (n = 21) and control pregnant subjects without any metabolic disease (n = 15). The T1DM group was divided into two subgroups of sufficient (SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Among the clinical and biochemical parameters that we collected, we found a negative statistical correlation between MPV and BMI, MPV and leptin, which are markers of obesity and insulin resistance. Additionally, we observed that MPV values were negatively correlated with GTT 2 h. Several studies showed that MPV is an important biological variable which predicts risk of vascular complications in diabetes such as the prothrombotic state [ 49 ]. In diabetic patients, the process of platelet-dependent thrombin formation is increased and fibrinolysis decreases [ 50 ].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Among the clinical and biochemical parameters that we collected, we found a negative statistical correlation between MPV and BMI, MPV and leptin, which are markers of obesity and insulin resistance. Additionally, we observed that MPV values were negatively correlated with GTT 2 h. Several studies showed that MPV is an important biological variable which predicts risk of vascular complications in diabetes such as the prothrombotic state [ 49 ]. In diabetic patients, the process of platelet-dependent thrombin formation is increased and fibrinolysis decreases [ 50 ].…”
Section: Discussionmentioning
confidence: 68%
“…Other studies showed that increased MPV and enhanced aggregation capacity lead to a pro-thrombotic state [ 52 ]. It is also demonstrated that in diabetic pregnant women with poor glycemic control, MPV is an easily measurable parameter that can predict a thrombotic state [ 49 ]. In patients with diabetes, over-activation of platelets plays an important role in pro-thrombotic events [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences between all the above reported studies could be related to study design, population sample size, and/or the nature and progression of disease among patients. In fact, a recent study demonstrated that poor glycemic control in diabetic patients could trigger, under certain conditions, a shift toward pro-thrombotic and anti-fibrinolytic states [ 48 ]. It is conceivable that the expression of ANXA5 on the cell surface is reduced due to inefficient shielding of negatively charged phospholipids from the blood; however, it is unclear whether the resulting endogenous pool of circulating ANXA5 could directly influence the development of atherosclerotic lesions or simply that changes in plasma levels during disease progression may be a consequence of the extent of vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that increased triglyceride levels in PCOS patients increased AUC30 and decreased the time of thrombus formation initiation (T10) and OT, but more research is needed to determine the usefulness of T-TAS in this group of patients [11]. On the other hand, Osiński et al [12] assessed whether in pregnant women with type 1 diabetes glycaemic control influences the prothrombotic and antifibrinolytic status. T-TAS (AR-chip) was used for the analysis to check if it is more sensitive than standard methods.…”
Section: Assessment Of Platelet Functionmentioning
confidence: 99%
“…The results indicated that T-TAS is better for the diagnosis of the prothrombotic state than, for example, activated partial thromboplastin time (APPT) or PT. Mean platelet volume (MPV) and D-dimer measurements can also be used to predict thrombotic status [12]. The blood glucose test was also undertaken by Yamamoto et al [13].…”
Section: Assessment Of Platelet Functionmentioning
confidence: 99%